Development and potential applications of gelatine, honey, and cellulose electrospun nanofibres as a green polymer / Nurul Haiza Sapiee, Nurul Atiqah Izzati Zulkifly and Noor Fitrah Abu Bakar - Sapiee, Nurul Haiza; Zulkifly, Nurul Atiqah Izzati; Abu Bakar, Noor Fitrah (Universiti Teknologi MARA, 2021)
Nanofibres have emerged as a brilliant technology to be applied in various areas due to their excellent properties that include having a great flexibility, prominent specific surface area and structural strength. Electrospinning is one of the most effective and favourable methods to fabricate nanofibres mainly because electrospun nanofibres have been demonstrated to possess small pore sizes, large specific surface area, and can be produced with different functions to fill the need of various applications in industries. Due to their remarkable properties, electrospun nanofibres have been proven to be suitable for applications in food packaging, medical, pharmaceutical and even in tissue engineering. Currently, there have been numerous research utilising both electrospun synthetic and natural polymers. Natural or green polymers are considered more favourable due to their biodegradable properties and potential biocompatibility. Therefore, there has been a shift to include more research regarding these green polymers. Green polymers can source from both plant polysaccharides and animal protein. Considering the different characteristics of synthetic polymers, the processing and fabrication methods may differ and must be adjusted accordingly. To well summarise the development of these green polymer nanofibres, we review fabrication methods of gelatine, honey and cellulose-based nanofibre and their potential applications in industries. There are indeed numerous promising areas for the usage of these green polymers which are based on their splendid individual properties especially when combined to form nanofibres via electrospinning. We hope this will promote continuous research and development for the applications in various industries including but not limited to tissue engineering, biomedical, food and pharmaceutical industries